A Revolution Against and for Public Sphere: Xin Hai Revolution’s Different Force on ‘Place’, also ‘Di Fang’ - Yixuan Zhao (Utan Kayu Publishing, 2024)
Modern 'Revolution' is always viewed as a force giving birth to publicity in urban areas. However, when come to the big cities in China before the 1911 revolution, the effect a be complicated due to its geopolitical situation. The South was the birthplace of revolutionary parties and receive a backlash from the 1911 revolution in terms of the destruction of Di Fang, a multi-layer system that enable self-governance of citizens; however, the north as the enemies of the revolution, the abdication of Qing æ¸… emperor release the public space for its citizens. The article takes Chengdu and Peiping as two cases respectively, to discuss the process.